Moving forward with complementary feeding: indicators and research priorities - Ruel, Marie T.; Brown, Kenneth H.; Caulfield, Laura E. (International Food Policy Research Institute, 2003)
For a number of reasons, progress in improving child feeding practices in the developing world has been remarkably slow. First, complementary feeding practices encompass a number of interrelated behaviors that need to be addressed simultaneously. Child feeding practices are also age-specific within narrow age ranges, which add to the complexity of developing recommendations and measuring responses. Finally, the lack of clear international recommendations for some aspects of complementary feeding has prevented the development of universal indicators to define optimal feeding. Without appropriate measurement tools, the design and evaluation of programs to improve complementary feeding practices cannot move forward. The present paper is the first systematic attempt at filling this gap. It puts forth a framework for the development of indicators of complementary feeding practices and proposes a series of possible indicators to measure some of the most critical aspects of infant and young child feeding. The emphasis is on simple indicators for use in large surveys or in program contexts. Indicators for the following aspects of complementary feeding of 6-23-month-old children are discussed: (1) breastfeeding; (2) energy from complementary foods; (3) nutrient density of complementary foods; and (4) safe preparation and storage of complementary foods. Finally, possible approaches to validate the proposed indicators are discussed and research priorities are highlighted.